2021
DOI: 10.1002/ajb2.1704
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the dioecious willow Salix purpurea

Abstract: The evolution of sex chromosomes is driven by sexual dimorphism, yet it can be challenging to document sexually dimorphic traits in dioecious plant species. At the genetic level, sexual dimorphism can be identified through sequence variation between females and males associated with sexually antagonistic traits and different fitness optima. This study aims to examine sexual dimorphism for 26 traits in three populations of Salix purpurea (a diversity panel and F 1 and F 2 populations) and determine the effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Also, homologous heterogametic transitions may be less likely induced by meiotic drive because the loci to restore the sex ratio need to arise on chromosomal regions unlinked to the sex determination region 48 . Notably, however, female sex ratio bias has been reported in several species in subgenus Vetrix [49][50][51][52][53] . Finally, the heterogametic transition in Salix may have resulted from solely from genetic drift, although under this model XY to ZW shifts are less common than XY to XY shifts unless extreme polygyny is present 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, homologous heterogametic transitions may be less likely induced by meiotic drive because the loci to restore the sex ratio need to arise on chromosomal regions unlinked to the sex determination region 48 . Notably, however, female sex ratio bias has been reported in several species in subgenus Vetrix [49][50][51][52][53] . Finally, the heterogametic transition in Salix may have resulted from solely from genetic drift, although under this model XY to ZW shifts are less common than XY to XY shifts unless extreme polygyny is present 54 .…”
Section: Discussionmentioning
confidence: 99%
“…They have the advantage of maintaining genetic diversity of species, which is beneficial to their adaption to different environments by natural selection or artificial selection during domestication of crops ( Barrett and Hough, 2013 ; Lei et al., 2017 ). Although sexual dimorphism in morphology ( Decraene and Smets, 1999 ; Barrett and Hough, 2013 ), physiology ( Laporte and Delph, 1996 ), timing of development ( Gouker et al., 2021 ) and resistance to stress ( Melnikova et al., 2017 ; Tonnabel et al., 2017 ; Liu et al., 2021b ) has been overwhelmingly reported, the relationship between metabolic profiles and microbial communities in roots and rhizosphere soils of dioecious plants has rarely been investigated. In the present study, we found that sex-based differences exhibited in metabolites and microbiota in dioecious papaya.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, gender-related plant responses are influenced by the environment [85,88,89]. In addition, reported data on the influence of gender on morphology is inconsistent and vary from having influence [90][91][92][93], being of uncertain influence [94][95][96] to no influence at all [97]. These inconsistencies can be particularly observed in the Populus genus, closely related genus to willows.…”
Section: Discussionmentioning
confidence: 99%